Genetic and Non-Genetic Factors Affecting Litter Size and Birth Weight of Rabbit in Minna, Niger State, Nigeria - Egena, SSA; Akpa, GN; Alemede, IC; Aremu, A (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2012)
Abstract. Genetic and non-genetic factors influencing litter size and birth weight of rabbit was evaluated using New Zealand White and Chinchilla breeds. Parameters measured were total number of kittens born per litter, number of litter born alive, live litter birth weight and average litter birth weight. Results of the experiment revealed that dam breed had no significant affect on total number of kittens born per litter, number of litter born alive and average litter birth weight while live litter birth weight were affected. Sire breed and month of birth did not significantly influenced all the parameters measured. Heritability estimates were low to moderate for all the traits (0.27 to 0.44), while repeatability estimates were observed to be low (0.17 to 0.26). No heritability and repeatability values were estimated for average litter birth weight of kittens due to negative genetic variance. Significant correlations were found between litter size traits and birth weight. Correlation between litter size traits and average litter birth weight, as well as live litter birth weight and average litter birth weight were observed to be non-significant.Keywords: rabbit, litter size, birth weight, genetic, non-geneticAbstrak. Faktor-faktor genetis dan non-genetis yang mempengaruhi litter size dan bobot lahir kelinci diteliti menggunakan kelinci bangsa New Zealand White and Chinchilla. Parameter yang diukur adalah jumlah anak sekelahiran, jumlah anak sekelahiran hidup, bobot lahir anak sekelahiran hidup, dan rataan bobot lahir anak sekelahiran. Hasilnya menunjukkan bahwa bangsa dari induk tidak berpengaruh secara nyata terhadap jumlah anak sekelahiran, jumlah anak sekelahiran hidup, rataan bobot lahir anak sekelahiran, sedangkan pengaruhnya terhadap bobot lahir anak sekelahiran hidup adalah nyata.Â Bangsa dari pejantan dan bulan saat kelahiran tidak berpengaruh pada semua peubah yang diukur. Taksiran heritabilitas pada semua peubah adalah rendah hingga sedang (0,27 - 0,44), sedangkan taksiran nilai repitabilitas adalah rendah (0,17 - 0,26). Nilai heritabilitas dan repitabilitas tidak diperoleh pada peubah rataan bobot lahir anak sekelahiran karena variansi genetisnya negatif. Korelasi yang nyata diperoleh pada jumlah anak sekelahiran dan bobot lahir. Korelasi yang tidak nyata diperoleh antara jumlah anak sekelahiran dengan rataan bobot lahir anak sekelahiran, serta bobot lahir anak sekelahiran hidup dengan rataan bobot lahir anak sekelahiran.Kata kunci: kelinci, jumlah anak sekelahiran, bobot lahir, genetis, non-genetisÂ SSA Egena et al/Animal Production 14(3):160-166, September 2012